The effect of peer feedback on students’ argumentative essay: A quasi experimental method at the fifth semester students of the English education department, educational sciences faculty Uin Syarif Hidayatullah Jakarta 2016 - Dewi, Ratna Sari (International Journal of Engineering and Technology, 2018)
The aim of this research was to know whether peer feedback gives an influence on students’ argumentative essay at the fifth semester of English Education Department in academic year 2016/2017. It was done from September until December 2016 ( four months ). The subjects of the research were 50 students from two classes. A quantitative research by using a quasi experimental post test only control group design was used to implement the research. The sampling technique used was purpose sampling. The instrument was test. Both students from the two classes were administered test of writing an argumentative essay. The data were analyzed by using T- Test. The mean score result of Pretest of class 5 B showed 68.36 , and mean score of class 5 C was 70.12. Then, the mean score result of post test of 5 B was 82.56, and for class 5 C was 76.92. Furthermore , based on the statistical calculation with the significance level of 5% and 1% , it showed that t - observation was higher than t - table that was 1.68 <5.64>2.41. Hence, there is an effect of peer feedback towards students’ argumentative essay.